Somatic Embryogenesis and Protoplast Isolation and Culture in Papaya (Carica Papaya L.) - Munari, Agus Sutanto (2001)
This study was carried out with the main objective of establishing somatic embryo production in papaya that may be used for further genetic improvement of the crop. The specific objectives were to induce somatic embryogenesis from immature zygotic embryos, to establish cell suspension culture of somatic embryos and to isolate and culture protoplasts from in vitro leaves. The first experiment studied the effect of growth regulators on the induction and regeneration of somatic embryos from immature zygotic embryos. The combinations of 2,4-dichlorophenoxyacetic acid (2,4-0) and 6-benzylaminopurine (BAP) at various concentrations were assessed in order to determine the best combination for somatic embryogenesis. The experiment was conducted in a Completely Randomized Design. The results showed that higher 2,4-D with or without BAP in the medium increased the percentage of somatic embryo formation and the number of somatic embryos per explant. MS medium supplemented with 5.0 mg/L 2,4-D promoted the highest percentage of somatic embryogenesis (74.55%), while the combinati on of 1.0 mg/L 2,4-0 and 0.01 mg/L BAP produced the highest percentage of callus formation (52. 58%). The highest number of somatic embryos per explant (66.61) was obtained when 5.0 mg/L 2,4-D and 0.01 mg/L BAP were added into MS medium. For germinati on of somatic embryos, the result was very inconsistent; nevertheless, the best treatment for plantlet formation was MS medium without growth hormone (NoBo). The second experiment was the establishment of cell suspensi on culture of somatic embryos. Four weeks after the transfer of somatic embryos into liquid MS medium containing 2.0 mg/L 2,4-0, pro-embryogenic masses (PEMs) were formed in the suspension. Maturation of embryos was achieved on transferring the heart-shaped embryos to liquid MS medium without growth regulator. Germination of somatic embryos occurred following the subculture of cotyledonary embryos from liquid MS medium with 0.2 mg/L BAP and 0.02 mg/L naphthalene acetic acid (NAA) to solid hormone-free MS medium.